PENGARUH BEBERAPA PAKET PEMUPUKAN DAN AMELIORASI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG TANAH (Arachis hypogaea L.) DI KAWASAN PENGEMBANGAN LAHAN GAMBUT [Effect of Amelioration and Fertilization Packages on Growth and Yield of Peanut (Arachis hypogaea L.) in Peat Land Development Area] - Nurzakiah, Siti; Koesrini, Koesrini; Anwar, Khairil (BERITA BIOLOGI, 2012)
Wetlands in Peatland Development Area has potential for the development of paddy, vegetables and palawija. Development of the commodities are limited or restricted by many limiting production factors such as nutrients, water and plant varieties. The purpose of this study is to know the influence of amelioration and fertilization packages on the growth and yield of peanuts in the swampland peat land development area. The treatments consisted of four amelioration and fertilization package i.e.: (1) Farmerâs package I: 250 kg.ha dolomite, (2) -1 -1 -1 -1 Farmerâs package II: 2.5 t.ha straw compost+18 kg.ha P2O5+300 kg.ha fly ash, (3) Recommendation package: 1.0 t.ha dolomite+22.5 -1 -1 -1 -1 -1 -1 kg.ha N + 36 kg.ha P2O5, and (4) Research package: 2.0 t.ha dolomite+22.5 kg.ha N+22.5 kg.ha P2O5 +30 kg.ha K2O. The result showed that the growth of plants (plant height and number of branches) does not differ between treatments, and the obtained peanut pod yield improvement is 50.45% in the research package treatment compared to Farmerâs package I.